2021
DOI: 10.5194/acp-21-18543-2021
|View full text |Cite
|
Sign up to set email alerts
|

Mercury isotopic compositions in fine particles and offshore surface seawater in a coastal area of East China: implications for Hg sources and atmospheric transformations

Abstract: Abstract. Isotopic compositions of Mercury (Hg) in atmospheric particles (HgPM) are probably the mixed results of emission sources and atmospheric processes. Here, we present Hg isotopic compositions in daily fine particles (PM2.5) collected from an industrial site (Chunxiao – CX) and a nearby mountain site (Daimeishan – DMS) in a coastal area of East China, and in surface seawater close to the industrial area, to reveal the influence of anthropogenic emission sources and atmospheric transformations on Hg isot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Most physical and chemical processes lead to MDF, but odd-MIF is mainly produced by photochemical reactions (e.g. photoreduction of aqueous Hg­(II), photodemethylation of methylmercury). Even-MIF is mainly observed in atmospheric samples, and its mechanism may be attributed to atmospheric redox processes. Previous studies have reported Hg isotopes of PBM in different regions (e.g., urban, rural, and coastal areas) , and seasonal even diurnal variation of odd-MIF ,, and indicate that the isotopic compositions of PBM emitted from primary sources would be modified during atmospheric transformation or transportation. However, the mechanism that drives Hg isotope variations of PBM is still poorly understood, especially during the transformations of PBM in severe haze events.…”
Section: Introductionmentioning
confidence: 99%
“…Most physical and chemical processes lead to MDF, but odd-MIF is mainly produced by photochemical reactions (e.g. photoreduction of aqueous Hg­(II), photodemethylation of methylmercury). Even-MIF is mainly observed in atmospheric samples, and its mechanism may be attributed to atmospheric redox processes. Previous studies have reported Hg isotopes of PBM in different regions (e.g., urban, rural, and coastal areas) , and seasonal even diurnal variation of odd-MIF ,, and indicate that the isotopic compositions of PBM emitted from primary sources would be modified during atmospheric transformation or transportation. However, the mechanism that drives Hg isotope variations of PBM is still poorly understood, especially during the transformations of PBM in severe haze events.…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, PBM samples collected at background sites (e.g., forested mountains and coastal/offshore sites) with low Hg levels commonly had distinctly positive Δ 199 Hg (0.15−0.66‰) values. 54,55,67,71,72,79 The isotope compositions of our TGM samples from the urban Wuda district partly overlapped those measured at urban/industrial sites of large cities in China and other countries (Figure 2). Specifically, our winter TGM samples with low Hg concentrations (1.32 ± 0.85 ng m −3 ) exhibited rather stable and small negative δ 202 Hg values (−0.65 ± 0.37‰), which are very similar to those of large Chinese cities such as Guiyang (−0.62 ± 0.25‰), Shijiazhuang (−0.56 ± 0.44‰), Jinan (−0.58 ± 0.43‰), Chengdu (−0.68 ± 0.44‰), and Wuhan (−0.70 ± 0.23‰).…”
Section: Comparison With the Global Atmospheric Hgmentioning
confidence: 64%
“…Atmospheric samples, including TGM (typically used to represent GEM) , , and PBM of different particulate sizes (TSP, PM 10 , and PM 2.5 ), ,,,, that were collected from diverse regions (urban/industrial, rural/background, and coastal/offshore sites) have been reported for Hg isotope compositions. TGM samples collected at inland background sites (e.g., forested mountains) far from the urban/industrial centers and tectonically active regions (e.g., volcanos and faults) are commonly characterized by positive δ 202 Hg (−0.16 to 1.19‰, site-specific mean values) and slightly negative Δ 199 Hg (−0.28 to −0.05‰) and Δ 200 Hg (−0.11 to −0.02‰) values (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been proven to be ideal for PM 2.5 sampling. 30,[47][48][49] In comparison, namely, PTFE lter is characterized by high blank value and hard to be digested, and PC, MCE, CA lters are not suitable for PM 2.5 sampling owing to their high-ow resistance and compactness (pore size of 0.45 mm). Therefore, the QM membrane lter was the best medium for collecting Sb from airborne particulate matter.…”
Section: Selection Of Membrane Lters and Sampling Timesmentioning
confidence: 99%